Curcumin mediated attenuation of carbofuran induced toxicity in the heart of Wistar rats - Jaiswal, S. K.; Gupta, V. K.; Siddiqi, N. J.; Sharma, B. (Cellular and Molecular Biology, 2017)
Carbofuran is used to improve the agricultural productivity as well as to protect the house hold and industrial products, but due to accumulation in the biological system, it causes serious side effects in many non-targets mammalian systems. The aim of present study is to evaluate the carbofuran induced oxidative stress in rat heart and its attenuation by using herbal product curcumin. Rats were divided into four groups; one group received 20 % LD50 of carbofuran another group of rats received same doses of carbofuran was  pretreated with curcumin (100 mg kg-1 body weight) and remaining two other groups served as control and curcumin treated animals. The activity of lactate dehydrogenase (LDH) in the heart tissues and serum was evaluated and the activity of enzymatic antioxidants superoxide dismutase (SOD) and catalase (CAT) was estimated in the heart tissues. The level of malondialdehyde (MDA) in heart tissues was also measured. The Total cholesterol (TC) and high density lipoprotein (HDL) was measured in the serum of the entire animals group. The results of present study showed that the activity of LDH in heart tissues were decreased and in serum was elevated. The MDA level was significantly elevated due to exposure of carbofuran. The enzymatic antioxidants, SOD and CAT activities were also inhibited. The ratio of pro-oxidant (P)/antioxidant (A) was also found to be sharply increased in the rat heart tissues of carbofuran exposed animals. The alterations in all the parameter were recovered by the pretreatment of curcumin (100 mg kg-1 body weight).